[Ag(OH2)2][Ag(SO4)2]: A Hydrate of a Silver(II) Salt. Issue 8 (19th December 2016) - Gilewski, Tomasz E.; Gawraczyński, Jakub; Derzsi, Mariana; Jagličić, Zvonko; Mazej, Zoran; Połczyński, Piotr; Jurczakowski, Rafal; Leszczyński, Piotr J.; Grochala, Wojciech
Abstract: When exposed to air at ambient conditions, AgSO4 slowly reacts with moisture, yielding AgSO4 ⋅H2 O. The crystal structure determination (powder data) shows that it may be described as [Ag(OH2 )2 ][Ag(SO4 )2 ], with some sulfate groups being shared between different Ag 2+ cations, resembling in that way its Cu 2+ analogue. [Ag(OH2 )2 ][Ag(SO4 )2 ], the first hydrate of a compound of Ag 2+, was extensively characterized using many physicochemical methods. Abstract : Past experience has shown that Ag 2+ and water are not compatible with each other, since redox reactions commence. AgSO4 ⋅H2 O, better described as [Ag(OH2 )2 ][Ag(SO4 )2 ], is the first compound that contains water molecules coordinated to the voracious Ag 2+ cation without undergoing decomposition. A combined experimental and theoretical study of the hydrate phase was carried out to confirm the structure.